Pengaruh Iklim Organisasi terhadap Kepuasan Kinerja Karyawan di PT PLN Cabang Lhokseumawe - Sullaida - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is intended to find ant organization climate (psychological dimension, structural dimension, social dimension and bureaucratic dimension) toward employee’s work satisfaction at PT. PLN Lhokseumawe branch. This research is also intended to find at dominant variable that influences employees’ work satisfaction at PT. PLN Lhokseumawe branch. This research is conducted at PT. PLN Lhokseumawe branch with population the whole employees’ with sample 66 employees’. The scope of the research is the influence of organization’s climate toward employee’s work satisfaction at PT. PLN (Persero) Lhokseumawe branch. Based on the result, all variables have siqnificant influence toward employees’ work satisfaction at PT. PLN Lhokseumawe branch. This can be seen from the value Fhitung = 57.714, while Ftabel at the siqnificant level α = 5 % equals to 2.53. the value R – Square or coefitien is determined 0,791. this show that 79,1 % variable is explained by un investigated variable. Based on partial test, it is found that all investigated variable have siqnificant influence toward employees’ work satisfaction because in this research all variable qets thitung > ttabel an siqnificant level α = 5 %.Keywords: Organization climate, employee’s